the role of international criminal policy in protecting the environment - Mohammed khaddar Kareem, Researcher; Hussein Hashemi, Dr. (lark, 2023)
The international community’s interest in the seriousness of environmental pollution emerged late, after finding itself besieged by pollution from all directions. Consequently, it began organizing conferences, and seminars, and signing numerous agreements to reach solutions and treatments for this problem. This is exemplified by the Stockholm Conference, Earth Summit, and other conferences. This environmental protection concern led to the establishment of international legal frameworks that focus on environmental protection, determining international responsibility for environmental issues and their impact on other countries. It emphasizes the importance of adhering to international law and rectifying the damages caused to the affected country as a result of environmental pollution, which exposes the lives and interests of its citizens to danger